Measurement of resonant and CP components in B[bar]0s→J=ψπ+π− decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
Structure of the decay ¯B0s→J/ψπ+π− is studied using data corresponding to 3 fb−1 of integrated luminosity from pp collisions produced by the LHC and collected by the LHCb detector. Five interfering π+π− states are required to describe the decay: f0(980),f0(1500),f0(1790),f2(1270), and f′2(1525). An alternative model including these states and a nonresonant J/ψπ+π− component also provides a good description of the data. Based on the different transversity components measured for the spin-2 intermediate states, the final state is found to be compatible with being entirely CP odd. The CP-even part is found to be <2.3% at a 95% confidence level. The f0(500) state is not observed, allowing a limit to be set on the absolute value of the mixing angle with the f0(980) of <7.7∘ at a 90% confidence level, consistent with a tetraquark interpretation of the f0(980) substructure.